Flirting with disaster ebook The charleston trilogy series, book 2. - WOODS, SHERRYL (Charleston Trilogy, 2005)
There's a fine line between desire and disaster. At least, that's what improper Southern belle Maggie Forsythe thinks when she' unceremoniously dumped by a fiance even her mother approved of. Maggie has never cared what anyone thinks, so why is she hiding away from her South Carolina Low Country home? Then an intervention by friends shows her she has options. Lots of them! And one includes a man who can make her forget all about being jilted. But one look at Maggie convinces project foreman Josh Parker that he's corn bread to her caviar. Sure, they have enough sparks to ignite a bonfire, but growing up broke has made him wary of sweet-tea-swilling debutantes. So why is he suddenly singing "Tea for Two"?